2017
DOI: 10.1371/journal.pone.0175028
|View full text |Cite
|
Sign up to set email alerts
|

Clown-care reduces pain in children with cerebral palsy undergoing recurrent botulinum toxin injections- A quasi-randomized controlled crossover study

Abstract: ObjectiveWe investigated the impact of clown-care on pain in 45 children with cerebral palsy who underwent recurrent Botulinum-toxin injections (age 7.04± 4.68 years). Participants were randomized to receive either clown (n = 20) or standard (n = 25) -care.MethodsPain Visual-Analogue-Scale (range 1–5) was reported before and after procedures. Pain assessment was lower for children undergoing Botulinum-toxin injections with clown-care (2.89± 1.36) compared to standard-care (3.85± 1.39; p = 0.036) even though pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
31
0
6

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(37 citation statements)
references
References 37 publications
0
31
0
6
Order By: Relevance
“…Quality assessment of level I to level III studies found ( n =number of studies): strong ( n =2), moderate ( n =12), and weak ( n =8) quality. Adequate conduct and report of appropriate statistical evaluation including power evaluations was described in nine studies . Suitable methods for controlling confounding variables and limiting potential biases were not reported in any studies.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Quality assessment of level I to level III studies found ( n =number of studies): strong ( n =2), moderate ( n =12), and weak ( n =8) quality. Adequate conduct and report of appropriate statistical evaluation including power evaluations was described in nine studies . Suitable methods for controlling confounding variables and limiting potential biases were not reported in any studies.…”
Section: Resultsmentioning
confidence: 99%
“…Management of procedural pain was evaluated for ( n =number of studies): intramuscular BoNT‐A injections ( n =5), acupuncture ( n =1), and venepuncture ( n =1) …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…3 Distraction techniques during the session help to relieve pain. 4 An anesthetic ointment type EMLA should be placed at the injection site 60' before injection. 5 In some difficult cases, a general anesthesia can be proposed.…”
Section: Clinical Usementioning
confidence: 99%
“…One study investigated the impact of clown interventions on pain during recurrent botulinum toxin injections in children with cerebral palsy [30]. A total of 45 children (aged 1.5-18 years) were randomized to receive either clown (n = 20) or standard care (n = 25).…”
Section: Presence Of Clown Doctors During Medical Proceduresmentioning
confidence: 99%